Comparative evaluation of sealing ability of light cure glass ionomer cement and light cure composite as coronal sealing material: An in vitro study - Pragya Jaiswal; Aditi Jain; Mahesh Motlani; Gunjan Agarwal; Vaibhav Sharma; Apoorva Bhatnagar (Journal of International Clinical Dental Research Organization, 2017)
Aim: To compare and evaluate the sealing ability of light cure composite and light cure GIC as coronal sealing materials. Materials and Methods: 30 extracted human teeth were divided into three experimental groups of 10 teeth each. The teeth in group I are obturated without coronal seal, teeth in group II are obturated with light cure GIC (3M ESPE VITREMER) as coronal seal and teeth in group III are obturated with light cure composite(3M ESPE filtek z250) as coronal seal, after removing 2mm of coronal gutta percha. These teeth (crown portion) are then suspended in methylene blue, sealed and kept for 72 hours, to observe the amount of dye penetration. After 72 hours teeth were removed, washed under running water, dried and sectioned longitudinally, separating buccal and lingual halves. The linear extent of dye penetration was measured from cavosurface margin of the access cavity to the most apical extent of dye penetration point. The length from the cavosurface margin to the apex of the tooth was also measured and percentage linear micro leakage was estimated. Statistical Analysis: Data was statistically analyzed using one-way ANOVA followed by Post-Hoc Multiple comparison (Bonferroni). Results: In the present study specimens in group I showed the maximum percentage of linear microleakage of 31.51 percent. The specimens in group II showed the minimal amount of linear micro leakage of 6.49 percent. Conclusion: It can be concluded coronal seal reduces the micro leakage, and light cure GIC has better coronal sealing ability.